Combustion performance and burnout characteristics of a 600 MW opposed wall-fired boiler under high ratio biomass co-firing - Xiangdong Li; Jing Pu; Yongzheng Gu; Jun Wang; Hanlin Zhang; Pengwei Yao; Zhiwei Wang; Gaofeng Dai; Jiaye Zhang; Xuebin Wang (Biomass and Bioenergy, 2027)

Freeze-thaw-induced greenhouse gas emissions from a Mollisol agroecosystem: Microbial and edaphic regulation under long-term agricultural management - Dan-Dan Wang; Shan-Shan Dai; Peng He; Zhi-Ming Zhang; Jian-Ying Zhou; Ming-Hui Liu; Shi-Xiu Zhang; Lu-Jun Li (Soil and Tillage Research, 2026)

Long-term organic fertilization fosters modular microbial networks: A global analysis of soil bacteriome responses - Shu-Le Li; Cai Chen; Xiang-Yu Dai; Hai-Song Yan; Yao-Yang Xu; Meili Feng; Jun He; Jianfeng Ren; Wan-Ying Xie; Fang-Jie Zhao (Soil Ecology Letters, 2026)

Enhancing soy protein interfacial properties: Structural modification using stirred media milling for improved high internal phase emulsion stabilization - Yanyao Cui; David Julian McClements; Jun Chen; Xingfeng Xu; Xixiang Shuai; Changhong Li; Qin Geng; Jialong Han; Taotao Dai (Food Hydrocolloids, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Nitrogen source composition shapes productivity–greenhouse gas trade-offs in saline–alkali rice systems - Xiang Zhang; Yang Liu; Jun Li; Xiaoyu Geng; Yue Jiang; Jizou Zhu; Lulu Wang; Weiyi Ma; Xiaozhou Sheng; Xiaoyong Qi; Yinglong Chen; Pinglei Gao; et al. (Agriculture, Ecosystems & Environment, 2026)

Freeze-thaw-induced destabilization of organic matter in Mollisols after decadal mineral fertilization - Dan-Dan Wang; Zhiming Zhang; Peng He; Shan-Shan Dai; Minghui Liu; Yu Luo; Tida Ge; Ekaterina Filimonenko; Yakov Kuzyakov; William R. Horwath; Lu-Jun Li (Soil Biology and Biochemistry, 2026)

Coupled mineral and microbial carbon pumps govern soil organic carbon accumulation in croplands at a large spatial scale - Shan-Shan Dai; Peng He; Zhiming Zhang; Dan-Dan Wang; Xuexian Zhang; Bingxue Zhu; Kaishan Song; Junjie Liu; Xia Zhu-Barker; Lu-Jun Li (Soil Biology and Biochemistry, 2026)

SnRK2 and MLKs orchestrate FREE1 nuclear retention through phosphorylation to regulate ABA signaling in Arabidopsis - Zien Li; Fanfan Qiao; Fei Rao; Juan Wei; Chuanliang Liu; Lei Feng; Jun Ma; Lu Dai; Lidan Zhang; Caiji Gao; Yanglan Liao; Wenjin Shen; et al. (Plant Science, 2026)

Garnet Sm-Nd dating reveals ca. 160 Ma lateral fluid pathway for stratiform Cu deposits in the Jianglang Dome, eastern Tibetan Plateau - Yudi Zhu; Xinwei Wang; Yanpei Dai; Changnan Wang; Tongzhu Li; Jun Liu; Xianglong Yu (Lithos, 2026)

Projecting flood exposure in China under future climate and population change: an age-structured analysis based on the SSP-RCP scenarios - Qian Yao; Can Lu; Mengya Li; Jiangyang Lin; Hanqing Xu; Dai Yamazaki; Jun Wang (Journal of Hydrology, 2026)

Machine learning-assisted Mn-N-C nanozyme colorimetric sensor array for trace-level detection of biogenic amines in meat - Jiajie Li; Changlong Dai; Shuyu Li; Zhuqian Xiao; Wei Wang; Huilin Zheng; Hongpeng Wang; Jun Huang (Food Chemistry, 2026)

Salinity-dependent optimization of organic nitrogen substitution improves yield formation and nitrogen use in rice - Xiang Zhang; Yue Jiang; Qingqing Ma; Xiaoyu Geng; Yang Liu; Jun Li; Yinglong Chen; Pinglei Gao; Huanhe Wei; Qigen Dai (Field Crops Research, 2026)

Soil erosion risk and prediction under land use changes based on RUSLE and PLUS models in the black soil region of Northeast China - Xuexian Zhang; Jiaoyang Zhang; Peng He; Shanshan Dai; Lu-Jun Li (CATENA, 2026)

G4 dimer-driven trimodal cross-validated immunosensing strategy for accurate CHI3L1 detection toward liver fibrosis diagnosis and drug efficacy evaluation - Lina Lu; Jiaxuan Qiao; Yaran Tao; Bingjun He; Jun Jiao; Mengai Yin; Fuju Dai; Yusheng Li; Lan Xue; Yu Zhu; Ye Huang; Qiang Chen (Chemical Engineering Journal, 2026)

Successful control of low-temperature sludge bulking in a WWTP by installing iron–carbon polyurethane packing in the return-sludge channel - Jiashu Dai; Jiahui Feng; Wei Wang; Xiaoyu Zhang; Zheng Gong; Yongjian He; Xiaoqian Wu; Jun Li (Water Research, 2026)

International roughness index prediction based on a TCN-BiGRU model optimized by an improved sooty tern optimization algorithm - Xun-Qian Xu; Jun-Hao Zhang; Li Dai; Jian Gong; Wen-Xuan Ge (Transportation Geotechnics, 2026)

Atmospheric deposition, aquatic transformation and marine carbon sequestration potential of black carbon: A critical review - Kexin Wu; Jianwei Xing; Jinming Song; Eric P. Achterberg; Xuegang Li; Jun Ma; Chenlong Feng; Shanshan Liu; Xingjian Xu; Jiajia Dai; Huamao Yuan (Marine Environmental Research, 2026)

Oat protein-EGCG-sugar beet pectin ternary complexes: Role of pectin in driving non-covalent interactions and improving functional properties - Zihao Chen; Muyao Luo; Taotao Dai; Min Fu; Zhaoying Li; Qin Geng; Jun Chen; Ti Li; Risi Wang (Food Hydrocolloids, 2026)

Multiscale spatial heterogeneity of sedimentary organic carbon in the intertidal zone of the Yellow River Estuary - Jun Ma; Zihe Zang; Yinyin Feng; Xiao Liu; Ludan Zhao; Xuegang Li; Lilian Wen; Jiajia Dai; Jianwei Xing; Baoxiao Qu; Huamao Yuan; Liqin Duan; et al. (Estuarine, Coastal and Shelf Science, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Acute alcohol exposure induces reproductive behavior defects, subfertility, brain transcriptomic changes of parental zebrafish and malformation in their offspring - Li Peng; Jun-Yuan Lei; Yue-Ying Meng; Shang-Chun Li; Xiang-Yan Dai (Toxicology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Nonlinear dynamics and optimal deployment of a deep-ocean mining riser with surface-mounted flow-disturbing robots - Shanfei Fan; Xiaoqiang Guo; Kelun Yang; Reza N. Jazar; Edson Denis Leonel; Nerguibaatar Tsend; Xianbin Liu; Yuwen Wang; Liming Dai; Jun Liu; Ning Zong; He Chen; et al. (Ocean Engineering, 2026)

Hydrate extraction riser gas-liquid-solid three-phase coupled flow simulation experiment: flow characteristics and prediction of flow pattern transition boundaries - Xiaoqiang Guo; Qi Gao; Yuechao Liu; Guanlong Jia; Ying Li; Jun Liu; Liming Dai; Ning Zong (Ocean Engineering, 2026)

Sediment heterogeneity shapes benthic microbial community assembly and co-occurrence network organization in the East China Sea - Lilian Wen; Jiajia Dai; Jinming Song; Xuegang Li; Huamao Yuan; Liqin Duan; Jun Ma (Marine Environmental Research, 2026)

Per- and polyfluoroalkyl substances and type 2 diabetes risk: Evidence from metabolomics and triglyceride-glucose index-related pathways - Jun Zhu; Yu Xia; Ningbin Dai; Wanying Wang; Zeyuan Chen; Weiyi Cao; Haibing Yang; Jing Shi; Fang Zhou; Liuqing Zhao; Lei Li; Zhan Zhang (International Journal of Hygiene and Environmental Health, 2026)

One-step method for modification of soy protein isolate and preparation of stable protein emulsions by industrial-scale high-energy fluidic microfluidizer - Zhaoying Li; Xiaofei Zeng; Taotao Dai; David Julian McClements; Yunfeng Lu; Xixiang Shuai; Lizhen Deng; Haolan Dong; Jun Chen (Food Chemistry, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Hydrodynamic characteristic of a deep-sea Mining Vehicle under wave Loading during deployment-retrieval phases - Xin Huang; Xiang Zhu; Yangrui Cheng; Jun Li; Yu Dai (Ocean Engineering, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Self-stabilization mechanism of whole soybean milk prepared by high-energy fluidic microfluidizer: The role of dietary fiber - Yuting Li; Yan Zhu; Taotao Dai; Lizhen Deng; Chengmei Liu; Jun Chen (Innovative Food Science & Emerging Technologies, 2026)

Structural modification of pea protein via high-energy fluidic microfluidizer: Mechanistic insights into enhanced solubility and acid-induced gelation properties - Zhaoying Li; Taotao Dai; Yunfeng Lu; Qin Geng; Xixiang Shuai; Zihao Chen; Lizhen Deng; Haolan Dong; Jun Chen (Food Research International, 2026)

A novel C17-sesquiterpene alkaloid derived from Dendrobium huoshanense : in vitro evaluation of its anti-lung cancer activity and molecular dynamics simulation study - Jun Chen; Xiu-Mei Li; Yong-Peng Sun; Ya-Feng Dai; Shi-Hao Li; Nai-Fu Chen; Nai-Dong Chen (Natural Product Research, 2026)

Conductive wire-activated iron–carbon potential: Self-driven bio-electrochemical system for efficient nitrogen and phosphorus removal from wastewater - Xiaoyu Zhang; Jiashu Dai; Jiahui Feng; Kuan Pan; Haifeng Wang; Guoqi Yan; Lili Zhang; Jun Li (Water Research, 2026)

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Engineering Ru–Co sites for promoted hydrogen spillover in ammonia synthesis - Shengxuan Luo; Guorun Dai; Annan Hu; Jun Cheng; Yuxiang Mao; Hao Li; Zhefeng Li; Weixin Liu; Rongxin Xia (Waste Disposal & Sustainable Energy, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Impacts of surface heterogeneity on energy partitioning in paddy ecosystems: A dual eddy covariance study - Yulong Dai; Bo Liu; Jun Wei; Yuanzhi Shi; Qilin Li; Fangping Liu; Yufeng Luo; Yuanlai Cui (Agricultural and Forest Meteorology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Self-calibrating ultrasensitive biosensing platform based on multifunctional nanocomposites and DNAzyme-assisted CRISPR/Cas12a system for accurate TGF-β1 quantification in liver fibrosis assessment - Lina Lu; Yaran Tao; Jiaxuan Qiao; Bingjun He; Yu Zhu; Fuju Dai; Tong Wang; Zhijie Wang; Xiangrui Wang; Yusheng Li; Jun Jiao; Lan Xue; et al. (Chemical Engineering Journal, 2026)

Insights from over a million births on maternal exposure to multiple pollutants and the risk of isolated ventricular septal defects - Xuelian Yuan; Li Dai; Ke Wang; Qi Li; Zhen Liu; Wenyan Li; Wenli Xu; Zhiyu Chen; Yuyang Gao; Jun Zhu; Hanmin Liu; Xiaohong Li (Environmental Pollution, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

Priming Effects on Soil Organic Matter Mineralization by Carbon Substrates: A Global Meta‐Analysis - Hongxin Dong; Yingyi Fu; Shanshan Dai; Peng He; Yu Luo; Margaret A. Oliver; William R. Horwath; Lu‐Jun Li (Global Change Biology, 2026)
Priming effects (PE) on soil organic matter (SOM) mineralization depend strongly on the type of carbon substrates added. It is crucial to understand the PE induced by various carbon substrates for predicting SOM dynamics and soil‐atmosphere carbon feedback. We conducted a meta‐analysis of 8015 observations from 283 articles to evaluate how carbon substrates (plant residues, root exudates, biochar, and degradable microplastics) regulate the mineralization of SOM through PE. Results demonstrated that all these types of carbon substrates increased SOM mineralization, which induced a positive PE. Plant residues induced the highest average PE, followed by root exudates, biochar, and degradable microplastics. Compared to soils without carbon substrate inputs, the rate of SOM mineralization increased by 113% in soil with cellulose‐rich non‐woody residues, whereas it increased by only 25% in soil with lignin‐rich woody residues. The mineralization of SOM increased by organic acids (151%) was greatest in root exudates, followed by monosaccharides (60%) and polysaccharides (12%). The strong mineralization induced by organic acids was probably related to the release of more mineral nutrients by reducing soil pH. The PE on SOM mineralization by woody biochar with high aromatic carbon content (48%) was greater than that of non‐woody biochar with high alkyl carbon content (43%). Microplastics with rapidly degradable polyhydroxyalkanoates induced more SOM mineralization (258%) than polybutylene succinate (61%) and polybutylene adipate‐co‐terephthalate (21%). The SOM priming was positively correlated with soil clay and incubation moisture, and negatively correlated with soil organic carbon, total nitrogen, soil C:N ratio, dissolved organic carbon, microbial biomass carbon, carbon input rate, incubation temperature, and soil depth. These results show that the positive PE is ubiquitous in soil ecosystems; its magnitude is linked intrinsically to the physicochemical characteristics and source of exogenous carbon substrate.

Y/Ho ratios in marine sediments unveil Neoproterozoic ocean acidification - Yong-Sheng Liu; Wen-Shuai Li; Jun-Bo Zhang; Jie Lin; Ao Yang; Lian Zhou; Dai-Du Fan; Xi Zhu; Ying-Hua Zhang (Science Bulletin, 2026)

Effect of pH-shifting combined with ultrasound treatment on the physicochemical, structural, and gelation properties of oxidized pea protein isolate - Qian Li; Siying Liu; Yi Cao; Yujie Cheng; Xudong Yan; Jun Chen; Taotao Dai; Peiyi Shen; David Julian McClements; Jian Xu; Ruiyun Chen (Food Hydrocolloids, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Explosive shock effects of type III hydrogen storage tank (70 MPa) with protective barriers: Full-scale explosion tests and fluid-solid coupling analysis - Haoshen Yu; Bei Li; Bing Han; Yan Liu; Xingtao Dai; Jun Hu; Jinyang Zheng; Linzhi Zou (Process Safety and Environmental Protection, 2026)

Potential impact of seamount on the mild oxygen minimum zone (OMZ) in the Western Pacific - Jun Ma; Lilian Wen; Xuegang Li; Kuidong Xu; Jiajia Dai; Yi Sun; Guorong Zhong; Detong Tian; Huamao Yuan; Liqin Duan; Jinming Song (Progress in Oceanography, 2026)

Impact of glycosylation position on functional characteristics and interaction mechanisms in pea protein-flavonoid complexes: A comparative study of genistein and its O-glycosides - Zihao Chen; Wuzhen Liu; Min Fu; Yuanrui Xu; Jun Chen; Qin Geng; Ti Li; Taotao Dai (Food Hydrocolloids, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

An agro-bionic approach to co-chelating ultrafine high-entropy metal phosphosulfide nanoparticles for superior Li/K-ion storage - Bing-Jie Feng; Jia-Jie Liu; Xiao-Hui Wu; Zhi-Qiang Gu; Li-Zhong Liu; Li-Bing Yang; Chen Dai; Ke Han; Ming-Jun Zhao; Wei-Jun Jiang; Yi Zhao (Chemical Engineering Journal, 2026)

Characteristics and driving factors of oceanic oxygen minimum zone (OMZ) in the context of global change - Jun Ma; Jinming Song; Xuegang Li; Huamao Yuan; Liqin Duan; Jiajia Dai; Lilian Wen (Science China Earth Sciences, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Research on the dynamic softening deformation characteristics and pore-water pressure response of warm frozen soil - Hu Zhang; Lijun Xing; Bo Zheng; Jintao Hu; Jun Zhao; Lang Dai; Zheng Li; Feng Liu (Cold Regions Science and Technology, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Expression and Characterization of Recombinant Triple Laterosporulin in Chlamydomonas reinhardtii - Bin Xue; Yang-Yang Li; Bei-Feng-Chu Zheng; Chan Zhang; Hadiatullah Hadiatullah; Wen-Ting Dai; Ya-Jun Wang; Zhen-Chuan Fan (Probiotics and Antimicrobial Proteins, 2026)

PLD3-mediated Mitophagy Attenuates Neuronal Ferroptosis and Promotes Functional Recovery after Spinal Cord Injury - Xintian Ding; Bin Dai; Jiafeng Peng; Kenan Sun; Shaoze Lan; Liu Yang; Canming Ye; Shenglong Pan; Chen Wang; Xinyu Liang; Ciren Lunzhu; Chun Chen; et al. (Molecular Neurobiology, 2026)

Optimisation of wheatgrass extraction using composite weighting-response surface methodology with phytochemical profiling and network pharmacology-based target prediction - Yanru Wang; Weiping Li; Meijuan Hou; Jun Su; Li Wu; Qirui Dai; Zeyu Wang; Danhong Wu (Natural Product Research, 2025)

Seismic performance and fragility assessment of BRBFs subjected to sequential earthquakes - Tao Li; Shijie Shu; Kurtulus Atasever; Kaoshan Dai; Oguz C. Celik; Jun Tang (Soil Dynamics and Earthquake Engineering, 2025)

Thermally stable ethylammonium doping strategy for pure red emission in CsPbI3 quantum dot light-emitting diodes - Jing Li; Xiuyuan Chen; Yifeng Feng; Xiaofeng Hu; Jialiang Liu; Jiajie Ye; Chenchen Yang; Qingquan He; Haiping He; Zhizhen Ye; Xingliang Dai; Jun Pan (Science Bulletin, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

Spatiotemporal variations in groundwater nitrate and its sources regulated by external inputs and soil profile characteristics in an agricultural basin - Kun Wang; Wanning Zhao; Jun Guo; Lei Yang; Shun Li; Jiulan Dai (Journal of Hazardous Materials, 2025)

Snowflake ZIF-8/Cu2S: A novel adsorbent material for efficient capture of radioactive iodine - Shu-Xuan Li; Xuan Zhao; Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Ao-Tian Gu; Peng Wang; Chun-Hui Gong; Ji-Gen Lu; Yi Yang (Journal of Environmental Chemical Engineering, 2025)

Enhancing pea protein functionality via media milling and pH-shifting - Changhong Li; Taotao Dai; Deyu Jiang; Yinong Feng; Lizhen Deng; Ti Li; Yihui Wang; Chengmei Liu; Jun Chen (Food Chemistry, 2025)

Comprehensive profiling of quinolone antibiotics in the Bohai Sea: Occurrence, source apportionment, and environmental risks - Lilian Wen; Jiajia Dai; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Chuanting Zhao; Jinming Song (Environmental Pollution, 2025)

Using explainable machine learning to better understand the environmental and socioeconomic contributions to preterm birth - Shuyu Li; Yuqing Dai; Ying Chen; Fang Liu; Jun Zhang (Environmental Pollution, 2025)

Sulfonamides as emerging contaminants in China's marginal seas: Distribution, Usage, and Residues - Jiajia Dai; Jinming Song; Lilian Wen; Jun Ma; Huamao Yuan; Xuegang Li; Liqin Duan; Qidong Wang (Continental Shelf Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

The dynamic changes and complex relationships of sustainable development goals in Tibet - Xian Li; Erfu Dai; Jun Yin; Lizhi Jia; Lin Zhao (Applied Geography, 2025)

Experimental study of a single sandwich unit and a multi-unit system using Peltier thermal switch in magnetic refrigeration - Hongmei Huang; Jun Shen; Zhenxing Li; Ke Li; Peng Hai; Wenshuai Zheng; Wei Dai (International Journal of Refrigeration, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Mapping snow cover frequency at 30 m for studying seasonal variations and topographic controls on the Tibetan Plateau - Guigang Wang; Tao Che; Liyun Dai; Yanxing Hu; Jun Wu; Saiyao Meng; Chuilei Kong; Jing Wang; Dongdong Feng; Shijie Wang; Xuemei Li (Journal of Hydrology, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Unveiling the characteristics of fluoroquinolones in China marginal seas: Spatiotemporal distribution, environmental fate, and mass inventory - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang; Chuanting Zhao (Marine Pollution Bulletin, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Effect of cation type on the formation, structure and functional properties of enzyme-crosslinked pea protein gels and emulsion gels - Xiaoxuan Yan; Shangdong Yan; Yi Cao; Yinxin Fu; Jun Chen; Taotao Dai; David Julian McClements; Qian Li (Food Chemistry, 2025)

Promoting flesh quality and fitness through intermittent fasting and dietary L-carnitine supplementation in Leiocassis longirostris - Zekun Weng; Jing Xu; Caijiao Dai; Qi Zeng; Lingkang Zhang; Yuejia Sun; Lijuan Li; Zemao Gu; Jun Yang; Junfa Yuan (Food Bioscience, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

The neglected effects of exogenous electrons on sludge humification during anaerobic digestion: Insights from digestate properties, electron transfer and microbial community - Lei Li; Jun Gao; Haoyu Liu; Hong Wang; Wan Yang; Shijie Yuan; Bin Dong; Yan Zhou; Xiaohu Dai (Chemical Engineering Journal, 2025)

A multi-effect synergistic photo-therapy PAS/ICG-Cu@ZOL hydrogel dressing with enhancing adaptive immunomodulatory and antibiofilm properties for improved healing of diabetic infected wounds - Bibo Ren; Jun Li; Kang Dai; Jiale Li; Chao Hu; Shiyu Wang; Kaijun Li; Zelin Ou; Haibo Wang (Chemical Engineering Journal, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Design and mechanism of ultra-flexible commercial solid-state lithium batteries over 10,000 dynamic bending cycles - Long Zhang; Kaixuan Zhou; Xinke Dai; Zhen Shang; Changjun Lu; Jun Li; Guoyong Huang; Shengming Xu (Chemical Engineering Journal, 2025)

Soil comammox Nitrospira dominates over ammonia-oxidizing archaea and bacteria in the invasion of Solidago canadensis - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Xiang-Zhen Li; Dao-Lin Du; Zhi-Cong Dai; Guang-Qian Ren; Xiao-Jun Zheng; Chao-Ying Liu (Plant and Soil, 2025)

Critical Threshold of Microbial Carbon Use Efficiency Regulates Soil Carbon Dynamics Under Solidago canadensis Invasion - Abdulkareem Raheem; Yijin He; Guanlin Li; Babar Iqbal; Qiuyue Zhang; Yi Tang; Sixuan Xu; Hyun-Jun Kim; Zhicong Dai; Jian Li; Xiaojun Zheng; Daolin Du (Journal of Soil Science and Plant Nutrition, 2025)

Ant colony-inspired cooperative control of multi- magnetorheological dampers system for coupled vibration mitigation of spatial irregular structures - Yang Yang; Zhao-Dong Xu; Xing-Huai Huang; Yao-Rong Dong; Jun Dai; Yuan-Jin Li (Engineering Structures, 2025)

Removal performance and mechanism of Bi2O3 for radioactive iodine in water: The role of crystal forms and oxygen vacancy - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2025)

SERS-based lateral flow immunoassay for rapid and sensitive sensing of nucleocapsid protein toward SARS-CoV-2 screening in clinical samples - Weixia Zhi; Lingwei Wang; Li Dai; Jing Xu; Tingting He; Xiangxin Zong; Jun Xu; Huaihong Cai; Jiang Pi; Pinghua Sun; Shanze Chen; Xueqin Huang; et al. (Analytica Chimica Acta, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

Efficient degradation of dodecyl dimethyl benzyl ammonium chloride by activated carbon-loaded nanoscale zero-valent iron activated persulfate - Min Li; Yibing Ma; Gui Ma; Mengjie Zhang; Qianlin Zuo; Gang Wang; Jun Ren; Tiaobin Zhao; Liang Dai (Journal of Water Process Engineering, 2025)

Occurrence, source, and enrichment process of cobalt from the Heiniudong metasedimentary rock-hosted stratiform Cu-Co polymetallic deposit, western Sichuan, China - Jun Liu; Wenchang Li; Qing Zhou; Tongzhu Li; Huihua Zhang; Yanpei Dai; Zhihui Dai; Zhanwu Shen; Dan Chen (Journal of Geochemical Exploration, 2025)

Association of organophosphate flame retardants exposure with liver function and the contrasting mediating roles of inflammatory and oxidative stress pathways - Yingyi Dai; Qin Li; Yongxian Li; Si Zhou; Xiaotong Li; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Pollution, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Polystyrene microplastics reduce honeybee survival by disrupting gut microbiota and metabolism - Han Li; Wangjiang Feng; Tong An; Pingli Dai; Yong-Jun Liu (Environmental Toxicology and Pharmacology, 2025)

Boosting electrochemical activity via manipulating the d-band center of CoNi2Se4/MXene heterostructure for supercapacitor application - Minmin Hu; Lihong Chen; Yu Wang; Jun Dai; Yifan Bi; Yuanming Li; Jian Zhao; Guicun Li; Lei Wang; Alan Meng; Zhenjiang Li (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

State-of-the-art review on liberation of cathode material in pretreatment recycling of spent lithium-ion battery - Chenye Wang; Ren Tao; Peng Xing; Jun Ni; Zhigen Cun; Shaojun Liu; Xingrui Wang; Yu Dai; Zhibin Long; Zhenhua Sun; Huiquan Li (Resources, Conservation and Recycling, 2025)

Low oxygen in the open ocean: A case study of mild oxygen minimum zone (OMZ) in the Western Pacific - Lilian Wen; Jun Ma; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Huamao Yuan; Jianwei Xing; Baoxiao Qu (Marine Environmental Research, 2025)

Antibiotic resistance genes (ARGs) in microorganisms and their indications for the nitrogen/sulfur cycle in the East China Sea sediments - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang (Journal of Hazardous Materials, 2025)

Mechanical properties and heavy metals immobilization of lithium slag stabilized by magnesium slag as road subbase material - Xuanhao Cao; Bowen Guan; Jincheng Yu; Jun Li; Wenbo Liu; Hua Zhao; Juanni Nian; Li Dai; Zheng Huang (Journal of Cleaner Production, 2025)

Assessing safety risks associated with Burkholderia gladiolus in soaked Auricularia auricula-judae: One instant predictive model study - Xiujin Chen; Minghui Dai; Li Bai; Jun Wang; Zixin Peng; Yang Qu; Shanshan Chen; Xianli Yang; Yalong Bai; Changyan Zhou; Yujuan Suo (International Journal of Food Microbiology, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Two unprecedented 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones with anti-Helicobacter pylori activity from agarwood of Aquilaria sinensis 'Reke 1' - Ke-Xin Qin; Hao Wang; Li Yang; Yan-Mei Wei; Cai-Hong Cai; Hui-Qin Chen; Wen-Hua Dong; Wei Li; Xian-Yun Yan; Jun Zeng; Wen-Li Mei; Jie Jian; et al. (Phytochemistry Letters, 2025)

Combined effects of microplastics and flupyradifurone on gut microbiota and oxidative status of honeybees (Apis mellifera L.) - Tong An; Wangjiang Feng; Han Li; Yanyan Wu; Pingli Dai; Yong-Jun Liu (Environmental Research, 2025)

Horizontally oriented 2D skin structures on fiber interface for long-life flexible energy storage devices - Guangyu Fang; Xiaorui Ma; Rong Hu; Jiao Dai; Haoran Tian; Lin Li; Weilin Xu; Yonggang Yao; Jun Wan (Chemical Engineering Journal, 2025)

Efficient perovskite solar cells with 70 % lead reduction enabled by dual-function Au@Ag@Ag2S plasmonic enhancer - Peiyu Li; Xinwei Li; Chunyan Dai; Guoge Zhang; Qifan Xue; Yanchun Liu; Jun Du; Nianqing Fu (Chemical Engineering Journal, 2025)

Enhancement of the rice protein solubility using industry-scale microfluidization and pH cycling: A mechanistic study - Zhaoying Li; Jun Chen; David Julian McClements; Yunfeng Lu; Aiping Fu; Qin Geng; Lizhen Deng; Ti Li; Chengmei Liu; Taotao Dai (Food Hydrocolloids, 2025)

Application of cellulose-rich organic resource improves soil quality and plant growth by recruiting beneficial microorganisms - Xing Zhou; Yuanyuan Yan; Ya Li; Liangliang Liu; Jun Zhou; Chuanchao Dai; Zucong Cai; Xinqi Huang (Applied Soil Ecology, 2025)

The carbon transport mediated by the mild oxygen minimum zone (OMZ) in the seamount area of the Western Pacific - Lilian Wen; Jun Ma; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Kuidong Xu; Jianwei Xing; Baoxiao Qu; Guorong Zhong (Marine Environmental Research, 2025)

Characterization of pea protein-different types of glycoside flavonoid complex interactions and functional properties - Zihao Chen; Min Fu; Jun Chen; Guowen Zhang; Qin Geng; Xing Hu; Yihui Wang; Ti Li; Ruihong Liang; Taotao Dai (Food Research International, 2025)

Construction of a reaction-based fluorescent sensor for tandem detection of Cu2+ and glutathione in wine - Han Yang; Renqiang Chen; Linjun Dai; Boquan Ren; Feng Yang; Yan-Jun Xu; Qing Li (Food Chemistry, 2025)

Improvement of rice protein functionality by electro-activation technology: Modulation of molecular and physicochemical properties - Wenhui Zhang; David Julian McClements; Jun Chen; Lizhen Deng; Yanyao Cui; Qin Geng; Ti Li; Chengmei Liu; Taotao Dai (Food Hydrocolloids, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Shelterbelt influence on soil microbial carbon and phosphorus limitation in farmland: Implications for soil health - Peng He; Xuechen Yang; Zhiming Zhang; Shan-Shan Dai; Mengyang You; William R. Horwath; Peng Zhang; Wenjie Wang; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2025)

Sex-linked DNA marker screening and characterization in albino northern snakehead (Channa argus var.) via third-generation sequencing and pool resequencing - Shengfei Dai; Mimi Chen; Shuqing Zheng; Jian Su; Jun Wu; Linqiang Han; Chaowei Zhou; Yuanchao Zou; Deshou Wang; Minghui Li (Aquaculture, 2025)

Enhanced biofilm-dependent biogas upgrading from waste activated sludge fermentation liquor in microbial electrolysis cells - Lei Li; Lezhu Su; Jun Gao; Shiyu Liu; Shijie Yuan; Nan Zhou; Zhi Zhou; Dongdong Wang; Yan Zhou; Xiaohu Dai (Water Research, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Glycated walnut meal peptide‑calcium chelates (COS-MMGGED-Ca): Preparation, characterization, and calcium absorption-promoting - Zilin Wang; Litong Liu; Haifen Jiang; Lingfei Li; Min Yang; Jiahe Dai; Liang Tao; Jun Sheng; Yang Tian (Food Chemistry, 2025)

A Review of Iron-Based Catalysts for Persulfate Activation to Remove PFAS in Water: Catalytic Effects of Various Iron Species, Influencing Factors and Reaction Pathways - Mengjie Zhang; YiYi Li; Xia Tian; Liang Dai; Gang Wang; Zhenle Lei; Gui Ma; Qianlin Zuo; Min Li; Mengmeng Zhao; Jun Ren (Water, Air, & Soil Pollution, 2025)

Dentate Gyrus Morphogenesis is Regulated by an Autism Risk Gene Trio Function in Granule Cells - Mengwen Sun; Weizhen Xue; Hu Meng; Xiaoxuan Sun; Tianlan Lu; Weihua Yue; Lifang Wang; Dai Zhang; Jun Li (Neuroscience Bulletin, 2025)
Autism Spectrum Disorders (ASDs) are reported as a group of neurodevelopmental disorders. The structural changes of brain regions including the hippocampus were widely reported in autistic patients and mouse models with dysfunction of ASD risk genes, but the underlying mechanisms are not fully understood. Here, we report that deletion of Trio , a high-susceptibility gene of ASDs, causes a postnatal dentate gyrus (DG) hypoplasia with a zigzagged suprapyramidal blade, and the Trio -deficient mice display autism-like behaviors. The impaired morphogenesis of DG is mainly caused by disturbing the postnatal distribution of postmitotic granule cells (GCs), which further results in a migration deficit of neural progenitors. Furthermore, we reveal that Trio plays different roles in various excitatory neural cells by spatial transcriptomic sequencing, especially the role of regulating the migration of postmitotic GCs. In summary, our findings provide evidence of cellular mechanisms that Trio is involved in postnatal DG morphogenesis.

Neutral purple soil acidification and mineralogical property changes due to long-term urea application in southwest China - Jun Xie; Dan Wang; Yuanxue Chen; Zhiqi Li; Wencai Dai; Rong Huang; Zifang Wang; Ming Gao (Soil and Tillage Research, 2024)

DNAJA1 regulates protein ubiquitination and is essential for spermatogenesis in the testes of mice and rats - Jing-jing Mao; Xiao-yu Dai; Yun-zi Liu; Li-jun Ren; Ji-qian-zhu Zhang; Lang Yan; Jin-feng Li; Yi-jun Tian; Jiang-bo Zhu; Ji-kuai Chen (Reproductive Toxicology, 2024)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Unveiling the susceptibility mechanism of Microcystis to consecutive sub-lethal oxidative stress—Enhancing oxidation technology for cyanobacterial bloom control - Fang Bai; Jie Li; Tianli Li; Jun Sha; Jin Liu; Lin Li; Guofei Dai; Yunlu Jia; Lirong Song (Journal of Hazardous Materials, 2024)

Characterization and emulsification of BSA/theaflavins complexes - Xiaoqiang Chen; Tianqi Fang; Xiulin Liu; Wei Feng; Tao Lu; Dechao Li; Lianxing Wang; Weilong Zhou; Xiaolei Lu; Jun Dai (Journal of Food Engineering, 2024)

Techno-economic and life cycle assessment for the zero-carbon emission process of the production of methanol from VOCs - Qiwei Luo; Qianyue Yu; Qingyang Li; Jun Wan; Yurui Wang; Baiqian Dai; Wenguo Xiang (Journal of Environmental Chemical Engineering, 2024)

Mechanistic studies on the alleviation of lipid accumulation and oxidative stress by Majia pomelo seed oil - Yidan Zhang; Zuzhen Dai; Shaomin Pu; Taotao Dai; Xixiang Shuai; Yihui Wang; Lizhen Deng; Risi Wang; Ruihong Liang; Ti Li; Jun Chen (Food Bioscience, 2024)

Elucidating the role of double-confined effect in hollow MOFs/GO catalytic membrane for deep arsenic pollution treatment - Jiangdong Dai; Lili Li; Xiaohua Tian; Ruilong Zhang; Dayi Yang; Qiaoyu Gao; Shuting Liu; Jun Zhao; Jian Ye; Xiaobo Zhang; Yi Wang (Desalination, 2024)

Microbial fuel cell-assisted composting shows stronger capacity to immobilize phosphorus: Emphasized on bacterial structures and functional enzymes - Hu Cui; Lei Li; Hao Zhou; Wei-Jun Zhang; Xiao-Hu Dai; Hui Zhu (Bioresource Technology, 2024)

Effects of cellulase treatment on properties of lignocellulose-based biochar - Bu Li; Yundong Liu; Wang Kai Tong; Jun Bo Zhang; Han Tang; Wenjuan Wang; Min-tian Gao; Chaomeng Dai; Nan Liu; Jiajun Hu; Jixiang Li (Bioresource Technology, 2024)

Melatonin Ameliorates Abnormal Sleep-Wake Behavior via Facilitating Lipid Metabolism in a Zebrafish Model of Parkinson’s Disease - Meng-Zhu Pang; Han-Xing Li; Xue-Qin Dai; Xiao-Bo Wang; Jun-Yi Liu; Yun Shen; Xing Xu; Zhao-Min Zhong; Han Wang; Chun-Feng Liu; Fen Wang (Neuroscience Bulletin, 2024)

Characterization and expression profiles of the ZmLBD gene family in Zea mays - Lidong Hao; Shifeng Li; Jun Dai; Li Wang; Zhibin Yan; Yunqiang Shi; Meiyu Zheng (Molecular Biology Reports, 2024)

Functional diversification of contact calls contribute to the cohesion of a multi-level society - Yi-Jun Yang; Ying Yan; Gu Fang; Yu-Ting Song; Jing Zang; Wen-Yong Tian; Dai-Bo Zhu; Paul A. Garber; Bao-Guo Li; Xiao-Guang Qi (Behavioral Ecology and Sociobiology, 2024)

Resistivity tomography based on multichannel electrodes - Fu-yu Jiang; Jiong Ni; Hai-jun Chen; Li-kun Gao; Song Chen; Xian-wei Wu; Zhi-qiang Su; Yao Lei; Ming-hui Dai; Run Han; Jun-kai Yu (Applied Geophysics, 2024)

Ecosystem Structure and Function in the Sea Area of Zhongjieshan Islands Based on Ecopath Model - Yao Qu; Zhongming Wang; Yongdong Zhou; Jun Liang; Kaida Xu; Yazhou Zhang; Zhenhua Li; Qian Dai; Qiuhong Zhang; Yongsheng Jiang (Journal of Marine Science and Engineering, 2024)
Based on the field survey and reference data of the sea area of the Zhongjieshan Islands from 2021 to 2022, the Ecopath model was used to analyze the energy flow structure of the marine ecosystem of the sea area of the Zhongjieshan Islands; the energy structure of the marine ecosystem was divided into 21 functional groups, and its nutrient structure, energy flow, and total system characteristics were analyzed. The results show that the credibility of the model is 0.414, which is at a medium level. The trophic level of each functional group of the ecosystem in the sea area of Zhongjieshan Islands was 1–3.48, the energy flow structure of the system was mainly concentrated in the first five grades, and the trophic level was relatively simple, with the average energy transfer efficiency of the system being 8.11%, the energy flow range being 2.81–13.04%, the energy transfer efficiency of the primary producers of the system being 7.25%, and the energy conversion efficiency of the system debris being 9.12%. The total system throughput was 2125.96 t·km−2; The analysis of the overall characteristics of the ecosystem showed that the system connectance index and the system omnivory index were 0.45 and 0.24, respectively, while the Finn’s cycling index was 8.24, the Finn’s mean path length of the system was 2.72, and the total primary production/total respiration was 1.71. In this study, the marine ecosystem model of the sea area of the Zhongjieshan Islands was studied to understand the trophic structure and ecosystem status of the sea area, which is conducive to the sustainable utilization and scientific management of fishery resources in the sea area.

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Antibiotic resistance genes (ARGs) and their eco-environmental response in the Bohai Sea sediments - Lilian Wen; Jiajia Dai; Jinming Song; Jun Ma; Xuegang Li; Huamao Yuan; Liqin Duan; Qidong Wang (Marine Pollution Bulletin, 2024)

Modulation of acid-induced pea protein gels by gellan gum and glucono-δ-lactone: Rheological and microstructural insights - Changhong Li; Taotao Dai; Deyu Jiang; Guowen Zhang; Lizhen Deng; Ti Li; Ruihong Liang; Hengtang Dai; Aiping Fu; Chengmei Liu; Jun Chen (Food Research International, 2024)

Black carp RNF135 enhances RIG-I-mediated antiviral signaling by facilitating its oligomerization - Chushan Dai; Yujia Miao; Zhan'ao Li; Yumian Liu; Ji Liu; Xiaoyu Liu; Shasha Tan; Hui Wu; Jun Xiao; Jun Zou; Hao Feng (Fish & Shellfish Immunology, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Understanding the mechanisms and potential pathways of soil carbon sequestration from the biogeochemistry perspective - Xiaojuan Feng; Guohua Dai; Ting Liu; Juan Jia; Erxiong Zhu; Chengzhu Liu; Yunpeng Zhao; Ya Wang; Enze Kang; Jun Xiao; Wei Li (Science China Earth Sciences, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Early Palaeozoic affinity of Hainan Island to Gondwana: New clues from metamorphic monazite and titanite of the Baoban Complex - Huiqing Ren; Jun Hu; Sanzhong Li; Dai Zhou; Ian Somerville; Lei Wang; Yongjiang Liu; Yanhui Suo; Shengyao Yu; Guozheng Sun; Xiangdong Wang (Lithos, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Magnetic porous microspheres altering interfacial thermodynamics of sewage sludge to drive metabolic cooperation for efficient methanogenesis - Hui Geng; Ying Xu; Rui Liu; Jun Xu; Xiang Li; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Different fates of particulate matters driven by marine hypoxia: A case study of oxygen minimum zone in the Western Pacific - Jun Ma; Lilian Wen; Xuegang Li; Jiajia Dai; Jinming Song; Qidong Wang; Kuidong Xu; Huamao Yuan; Liqin Duan (Marine Environmental Research, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

Effects of foliar selenium, biochar, and pig manure on cadmium accumulation in rice grains and assessment of health risk - Ofori Prince Danso; Zhangmin Wang; Zezhou Zhang; Shanshan Niu; Yuanqi Wang; Gege Wu; Xiaohu Wang; Li Zheng; Jun Dai; Xuebin Yin; Renbin Zhu (Environmental Research, 2024)

Interconnected pyrolysis and activation with in-situ H3PO4 activation of biochar from pear wood chips in a pilot scale dual fluidized bed - Yuanxiang Chen; Chunbao Zhou; Xuyang Xing; Lei Chen; Bang Yao; Li Chao; Yingwen Zhang; Jun Wang; Jie Dong; Chenglong Liu; Jianjun Dai (Chemical Engineering Journal, 2024)

Weakly hydrophobic microenvironment-assisted membrane-based confined catalysis for efficient organoarsenic contamination removal - Jiangdong Dai; Lili Li; Qihan Fang; Xiaohua Tian; Ruilong Zhang; Jianming Pan; Jun Zhao; Yi Wang; Jian Ye (Chemical Engineering Journal, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

A novel zwitterionic magnetic nanocomposite developed for non-invasive speciation analysis of inorganic chromium - Faisal Faiz; Yi-fan Pan; Sen Zhang; Jinxia Dai; Jun-qin Qiao; Hong-zhen Lian; Li Mao; Xiao-bing Cui (Journal of Hazardous Materials, 2024)

Activated carbon/persulfate-driven in-situ remediation of naphthalene-polluted groundwater: Insights into active sites, passivation-activation mechanisms and practical applications - Chaomeng Dai; Jun Bo Zhang; Jia Jie Zou; Jiajun Hu; Min-tian Gao; Zhi Li; Yucang Liang; Lang Zhou (Journal of Environmental Chemical Engineering, 2024)

Production of aromatic-rich oil from marine oily sludge via in situ catalytic pyrolysis using coal gangue - Chenglong Liu; Dekai Fan; Yang Liu; Chunbao Zhou; Li Chao; Bang Yao; Yingwen Zhang; Jianjun Dai; Lei Chen; Jie Dong; Jun Wang; Xuyang Xing; et al. (Fuel, 2024)

Acid-induced pea protein gels pretreated with media milling: Gelling properties and the formation mechanism - Changhong Li; Taotao Dai; Deyu Jiang; Qin Geng; Lizhen Deng; Ti Li; Junzhen Zhong; Chengmei Liu; Jun Chen (Food Chemistry, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

A DNA walker based on hairpin-shaped DNA aligner and fueled by nicking endonuclease for sensitive and rapid miRNA analysis - Ting Huang; Zhenbang Lu; Peixian Mo; Piao Liu; Simin Liu; Jing Peng; Rongtian Li; Nuan Jia; Minmin Li; Zong Dai; Jun Chen; Jinxiang Chen (Analytica Chimica Acta, 2024)

Parotid Gland Segmentation Using Purely Transformer-Based U-Shaped Network and Multimodal MRI - Zi’an Xu; Yin Dai; Fayu Liu; Siqi Li; Sheng Liu; Lifu Shi; Jun Fu (Annals of Biomedical Engineering, 2024)

Multiple stresses induced by chronic exposure to flupyradifurone affect honey bee physiological states - Jin Chen; Yong-Jun Liu; Qiang Wang; Li Zhang; Sa Yang; Wang-Jiang Feng; Min Shi; Jing Gao; Ping-Li Dai; Yan-Yan Wu (Science of The Total Environment, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Spatio-temporal differences and simulation studies of the carbon budget from fisheries in the northern marine economic circle of China - Dai Jia; Xinyu Liu; Xin Guan; Jinfei Guo; Shuqi Zhang; Haozheng Li; Yiyang Jin; Jun Sun (Frontiers in Marine Science, 2024)
With the proposal of dual carbon goals, enhancing carbon sinks and reducing carbon emissions has become a critical issue. Fisheries, as a component of agriculture, possess the dual attributes of being a “carbon sink” (biological carbon fixation) and a “carbon source” (the carbon emissions from fishing vessels). Therefore, it is necessary to assess the carbon sink and carbon emission levels of fisheries. The northern marine economic circle, which includes Liaoning, Hebei, Tianjin, and Shandong, is an important site for fisheries in China, characterized by abundant aquatic resources. However, a comprehensive assessment of the carbon budget for fisheries in this region is still unclear. This study calculated the carbon sinks, carbon emissions, and net carbon emissions associated with fisheries in the region from 2013 to 2020. Additionally, we used sensitivity analysis and scenario simulation to explore the factors influencing the net carbon emissions. The results revealed that the carbon budget of the northern marine economic circle was in a carbon deficit (the amount of carbon emissions was higher than that of carbon sinks) from 2013 to 2020. However, a downward trend in the net carbon emissions was observed, indicating the potential of achieving carbon neutrality. From the perspective of provinces, significant differences among provinces (cities) were found in terms of carbon sinks, carbon emissions, and net carbon emissions, with Shandong having the largest net carbon emissions. Furthermore, the production of clams and the use of seawater trawl net have a significant impact on the net carbon emissions. Increasing the production of clams while reducing the power of trawling operations can significantly decrease net carbon emissions. Based on these results, this study provides relevant suggestions to enhance the carbon sink capacity and decrease the carbon emissions of fisheries in the northern marine economic circle.

Asp-tRNAAsn/Glu-tRNAGln amidotransferase A subunit-like amidase mediates the degradation of insecticide flonicamid by Variovorax boronicumulans CGMCC 4969 - Xue-Xiu Yu; Ke-Xin Chen; Pan-Pan Yuan; Yu-He Wang; Hua-Xiao Li; Yun-Xiu Zhao; Yi-jun Dai (Science of The Total Environment, 2024)

Clean and efficient preparation of metallic bismuth from methane-sulfonate electrolyte in the membrane electrolysis cell - Cong Chang; Shenghai Yang; Jie Dai; Jun Li; Caiping Fu; Jingtao Cui; Weizhi Zeng; Hong Liu; Jiaqi Qi; Wei Jin; Yongming Chen (Journal of Environmental Chemical Engineering, 2024)

Development and experimental analysis of a multi-bed active magnetic regenerator - Peng Hai; Jun Shen; Zhenxing Li; Ke Li; Wei Dai (International Journal of Refrigeration, 2024)

A macromolecular Gleditsia Saponin induces apoptosis of leukemia cells through Fas-mediated death receptor pathway and mitochondrial pathway - Wen-jie Ding; Yao Huo; Zhen-tong Li; Yan-ru Liu; Ke-yao Dai; Chao Liu; Hai-yu Ji; An-jun Liu (Food Bioscience, 2024)

Emulsion stability enhancement against storage and environment stresses using complex plant protein and betanin - Qin Geng; Ting Hu; Jun Chen; Changhong Li; Ti Li; Xuemei He; Jialong Han; Chengmei Liu; Taotao Dai (Food Bioscience, 2024)

Design and synthesis of novel factor XIa Inhibitors with bicyclic isoquinoline and naphthalene fragments - Yi Zhang; Linjun Dai; Yi Tan; Yongpeng Yu; Junhao Xing; Feng Yang; Boquan Ren; Yan-Jun Xu; Qing Li (Medicinal Chemistry Research, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

STON2 variations are involved in synaptic dysfunction and schizophrenia-like behaviors by regulating Syt1 trafficking - Yuanlin Ma; Kai Gao; Xiaoxuan Sun; Jinxin Wang; Yang Yang; Jianying Wu; Anping Chai; Li Yao; Nan Liu; Hao Yu; Yi Su; Tianlan Lu; et al. (Science Bulletin, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Enhancement of foamability parallel with foam stability of rice dreg protein by ions-induced treatment based on pH shifting: Interfacial properties and interaction mechanism - Sha Yang; Jun Chen; Gaomeng Xu; Lizhen Deng; Changhong Li; Ti Li; Chengmei Liu; Taotao Dai (Food Hydrocolloids, 2024)

Testing for adaptive changes linked to range expansion following a single introduction of the fall webworm - Jin‐Xu Dai; Li‐Jun Cao; Jin‐Cui Chen; Fangyuan Yang; Xiu‐Jing Shen; Li‐Jun Ma; Ary Anthony Hoffmann; Min Chen; Shu‐Jun Wei (Molecular Ecology, 2024)
Adaptive evolution following colonization can affect the impact of invasive species. The fall webworm (FWW) invaded China 40 years ago through a single introduction event involving a severe bottleneck and subsequently diverged into two genetic groups. The well‐recorded invasion history of FWW, coupled with a clear pattern of genetic divergence, provides an opportunity to investigate whether there is any sign of adaptive evolution following the invasion. Based on genome‐wide SNPs, we identified genetically separated western and eastern groups of FWW and correlated spatial variation in SNPs with geographical and climatic factors. Geographical factors explained a similar proportion of the genetic variation across all populations compared with climatic factors. However, when the two population groups were analysed separately, environmental factors explained more variation than geographical factors. SNP outliers in populations of the western group had relatively stronger response to precipitation than temperature‐related variables. Functional annotation of SNP outliers identified genes associated with insect cuticle protein potentially related to desiccation adaptation in the western group and genes associated with lipase biosynthesis potentially related to temperature adaptation in the eastern group. Our study suggests that invasive species may maintain the evolutionary potential to adapt to heterogeneous environments despite a single invasion event. The molecular data suggest that quantitative trait comparisons across environments would be worthwhile.

Nutrient characteristics driven by multiple factors in large estuaries during summer: A case study of the Yangtze River Estuary - Lilian Wen; Jinming Song; Jiajia Dai; Xuegang Li; Jun Ma; Huamao Yuan; Liqin Duan; Qidong Wang (Marine Pollution Bulletin, 2024)

Hypoxia preconditioning of human amniotic mesenchymal stem cells enhances proliferation and migration and promotes their homing via the HGF/C-MET signaling axis to augment the repair of acute liver failure - Qian Wang; Yuwen Li; Hui Yuan; Linya Peng; Zixing Dai; Ye Sun; Rui Liu; Wenting Li; Jun Li; Chuanlong Zhu (Tissue and Cell, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Middle to late Holocene hydroclimate instability in the Yangtze River Delta region of China inferred from phytolith records, and its implications for societal disruption - Li Xueming; Liu Yan; Jiang Jun; Dai Jinqi; Xiao Li; Zhang Xiaoyu; Zhao Xiaoshuang; Chen Jing; Liu Shihao; Zhao Ning; Sun Qianli (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Positive effects of biochar application and Rhizophagus irregularis inoculation on mycorrhizal colonization, rice seedlings and phosphorus cycling in paddy soils - Yixuan CHEN; Zhonghua WEN; Jun MENG; Zunqi LIU; Jialong WEI; Xiyu LIU; Ziyi GE; Wanning DAI; Li LIN; Wenfu CHEN (Pedosphere, 2024)

Iron isotopic compositions of HIMU Ocean island basalts: Implications for the mantle source lithology - Cheng-Cheng Dai; Xiao-Jun Wang; Li-Hui Chen; Takeshi Hanyu; Xiao-Yu Zhang; Gang Zeng; Lie-Wen Xie (Lithos, 2024)

A review of the influence of environmental pollutants (microplastics, pesticides, antibiotics, air pollutants, viruses, bacteria) on animal viruses - Tong Li; Ruiheng Liu; Qian Wang; Jiaqian Rao; Yuanjia Liu; Zhenkai Dai; Ravi Gooneratne; Jun Wang; Qingmei Xie; Xinheng Zhang (Journal of Hazardous Materials, 2024)

Improving food sustainability by converting orange peel waste products into hydrogels using stirred media milling - Changhong Li; David Julian McClements; Taotao Dai; Deyu Jiang; Lizhen Deng; Chengmei Liu; Jun Chen (Journal of Food Engineering, 2024)

Improved umami taste of the enzymatic hydrolysate of soybean protein isolate by Corynebacterium glutamicum P-45 fermentation - Lingling Shangguan; Zixiong Liu; Huiyan Zhang; Qiao Yang; Xiaoling Zhang; Lan Yao; Pei Li; Xiong Chen; Jun Dai (Food Bioscience, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

An organic acid-alkali coordinately regulated liquid electrolyte enables stable cycling of high-voltage proton battery - Huige Ma; Mingsheng Yang; Rui Li; Yan Wang; Liping Zheng; Xiaoming Jing; Yuxing Hao; Yujie Dai; Jiefeng Gao; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2024)

Immune-enhanced and tumor-targeted PDT cascade therapy for oral squamous cell carcinoma utilizing a carrier-free BRD4 inhibitor/PDT agent nanocomplex - Jiechen Liu; Guangrui Liu; Chunlei Dai; Jun Wu; Qing Li (Chemical Engineering Journal, 2024)

Correction to: Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Individual and combined effects of earthworms and Sphingobacterium sp. on soil organic C, N forms and enzyme activities in non-contaminated and Cd-contaminated soil - Li Jia; Qing Liu; Siyi Chen; Kexue Liu; Yiqing Chen; Mikael Motelica-Heino; Hesen Zhong; Menghao Zhang; Cevin Tibihenda; Patrick Lavelle; Jun Dai; Chi Zhang (European Journal of Soil Biology, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Recent advances in starch-based coatings for the postharvest preservation of fruits and vegetables - Limin Dai; Xiuzhuang Wang; Xiayu Mao; Linyu He; Changwei Li; Jun Zhang; Yuan Chen (Carbohydrate Polymers, 2024)

Two unprecedented 2-(2-phenethyl)chromone dimers from red soil agarwood of Aquilaria crassna - Hong-Xing Chai; Hao Wang; Jun Zeng; Wen-Hua Dong; Wen-Li Mei; Bei Jiang; Wei Li; Hao-Fu Dai (Phytochemistry Letters, 2024)

High energy media mill modified pea dietary fiber: Physicochemical property and its mechanism in stabilizing pea protein beverage - Yuting Li; Yuqi Tian; Lizhen Deng; Taotao Dai; Chengmei Liu; Jun Chen (Food Hydrocolloids, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

pH-responsive bentonite nanoclay carriers control the release of benzothiazolinone to restrain bacterial wilt disease - Liang Yang; Yao Wang; Yijia Liang; Haibin Deng; Jun Wang; Yuhao Dai; Fuyou Guo; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2024)

Label-free fluorescence detection of human 8-oxoguanine DNA glycosylase activity amplified by target-induced rolling circle amplification - Mengxu Sun; Xiao Chen; Xiang Chen; Qianying Zhou; Ting Huang; Tong Li; Baoping Xie; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Analytica Chimica Acta, 2024)

Modification of flavonoids: methods and influences on biological activities - Changhong Li; Taotao Dai; Jun Chen; Mingshun Chen; Ruihong Liang; Chengmei Liu; Liqing Du; David Julian McClements (Critical Reviews in Food Science and Nutrition, 2023)

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Investigation on toxicity and mechanism to Daphnia magna for 14 disinfection by-products: Enzyme activity and molecular docking - Jin J. Li; Min J. Dai; Jun Z. Xue (Science of The Total Environment, 2023)

Ultrafiltration fractionation of rice protein hydrolysates: Physicochemical properties and potential biological activities of different rice protein hydrolysate fractions - Ruiyu Song; Taotao Dai; Lizhen Deng; Yingying Ke; Ti Li; Chengmei Liu; Jun Chen (Food Bioscience, 2023)

Enhancing the dispersibility of commercial pea protein ingredients using stirred media milling: Potential mechanisms of action - Changhong Li; David Julian McClements; Taotao Dai; Lizhen Deng; Zhi Feng; Ti Li; Chengmei Liu; Jun Chen (Food Hydrocolloids, 2023)

Analysis of coumarin content and key enzyme genes expression involved in coumarin biosynthesis from Peucedanum praeruptorum Dunn at different stages - Peipei Wei; Yaobiqi Li; Cheng Song; Muhammad Aamir Manzoor; Jun Dai; Qihui Yin; Yanmei Zhang; Bangxing Han (Acta Physiologiae Plantarum, 2023)

Distribution patterns of six metals and their influencing factors in M4 seamount seawater of the Western Pacific - Jun Ma; Xuegang Li; Jinming Song; Lilian Wen; Xianmeng Liang; Kuidong Xu; Jiajia Dai (Marine Pollution Bulletin, 2023)

Prognostic value of left ventricular systolic function on moderate aortic stenosis: the China-VHD study - Xianbao Liu; Qifeng Zhu; Qiong Liu; Haiyan Xu; Hanyi Dai; Yaoyao Zhou; Jun Chen; Stella Ng; Ye Lu; Yanyan Zhao; Zhe Li; Yongjian Wu; et al. (Science Bulletin, 2023)

Low-temperature degradation of lignin in aprotic solvent system for preparation of monophenolic platform chemicals - Xu Zeng; Yan Xu; Qiqi Dai; Jiaqi Li; Qixuan Lin; Jun Ye; Chuanfu Liu; Wu Lan (Chemical Engineering Journal, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Genome analysis of Tepidibacter sp. SWIR-1, an anaerobic endospore-forming bacterium isolated from a deep-sea hydrothermal vent - Xue-Gong Li; Jie Dai; Wei-Jia Zhang; Ai-Jun Jiang; Deng-Hui Li; Long-Fei Wu (Marine Genomics, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Comparative study of continuous and batch microwave-assisted pyrolysis of waste printed circuit boards: product characteristic, bromine transformation, and energy efficiency assessment - Chunbao Zhou; Yingwen Zhang; Xuyang Xing; Tianhao Zhang; Asif Ali Siyal; Yang Liu; Jianjun Dai; Junshen Qu; Chenglong Liu; Bang Yao; Li Chao; Lei Chen; et al. (Journal of Cleaner Production, 2023)

Oral bovine serum albumin administration alleviates inflammatory signals and improves antioxidant capacity and immune response under thioacetamide stress in blunt snout bream fed a high-calorie diet - Kenneth Prudence Abasubong; Guang-Zhen Jiang; Hui-xing Guo; Xi Wang; Yang-yang Huang; Yong-Jun Dai; Xiang-Fei Li; Yan-zou Dong; Ndakalimwe Naftal Gabriel; Wen-bin Liu (Fish & Shellfish Immunology, 2023)

Acceleration of nitrogen removal performance in a biofilm reactor augmented with Pseudomonas sp. using polycaprolactone as carbon source for treating low carbon to nitrogen wastewater - Xiujie Wang; Huimin Hou; Peizheng Liu; Liangang Hou; Tongyi Yang; Hongliang Dai; Jun Li (Bioresource Technology, 2023)

Impacts of land-use change on carbon dynamics in China's coastal wetlands - Li-Shan Tan; Zhen-Ming Ge; Shi-Hua Li; Ke Zhou; Derrick Y.F. Lai; Stijn Temmerman; Zhi-Jun Dai (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Effects of functional group loss on biochar activated persulfate in-situ remediation of phenol pollution in groundwater and its countermeasures - Chaomeng Dai; Jun Bo Zhang; Min-tian Gao; Yalei Zhang; Jixiang Li; Jiajun Hu (Journal of Environmental Management, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Field Measurement and Theoretical Analysis of Sidewall Roughness on Shaft Resistance of Rock-Socketed Piles - Jun Liu; Zhongwei Li; Guoliang Dai; Weiming Gong (Journal of Marine Science and Engineering, 2023)
Sidewall roughness is a key factor influencing the shaft resistance of rock-socketed piles. Owing to the difficulties in onsite measuring and the inconsistency in quantitatively characterizing the roughness degree of sidewalls, existing approaches for estimating the shaft resistance of rock-socketed piles often cannot take this factor into account. Based on the measured surface curves of the 68 sockets in No. 6# and 7# group piles of the Chishi Bridge on the Ru-Chen Expressway in China, sidewall roughness is described by introducing the roughness factor (RF) based on the Horvath and Monash models, respectively, while a statistical analysis of the sidewall roughness in rock-socketed sections is also conducted. In addition, an analytical solution to the shaft resistance of rock-socketed piles with consideration of sidewall roughness and the relative settlement of the pile–rocks interface (∆s), is proposed and further compared with the field load tests. The results showed that: the RF obtained by the Horvath model is bigger than that obtained by the Monash model; the larger RF is, the bigger the mobilized shaft resistance; the analytical solution generally overestimates the mobilized shaft resistance of rock-socketed piles under the same ∆s, and the deviation is less than 15% if ∆s is larger than 3.00 mm. The Horvath model is recommended to quantitatively characterize the roughness degree of sidewalls for its good operability in practice.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Seismic performance of RC frames with self-centering precast post-tensioned connections considering the effect of infill walls - Kaoshan Dai; Tongfei Sun; Ye Liu; Tao Li; Jun Xu; Matiyas A. Bezabeh (Soil Dynamics and Earthquake Engineering, 2023)

Thiacloprid impairs honeybee worker learning and memory with inducing neuronal apoptosis and downregulating memory-related genes - Airui Li; Linghong Yin; Li Ke; Qing-Yun Diao; Yanyan Wu; Pingli Dai; Yong-Jun Liu (Science of The Total Environment, 2023)

Blood-based biomarkers for Alzheimer’s disease: a multicenter-based cross-sectional and longitudinal study in China - Feng Gao; Linbin Dai; Qiong Wang; Chang Liu; Kexue Deng; Zhaozhao Cheng; Xinyi Lv; Yan Wu; Ziyi Zhang; Qingqing Tao; Jing Yuan; Shiping Li; et al. (Science Bulletin, 2023)

Acute and chronic effects of sublethal neonicotinoid thiacloprid to Asian honey bee (Apis cerana cerana) - Min Shi; Yi Guo; Yan-Yan Wu; Ping-Li Dai; Shao-Jun Dai; Qing-Yun Diao; Jing Gao (Pesticide Biochemistry and Physiology, 2023)

Risk assessment models of power transmission lines undergoing heavy ice at mountain zones based on numerical model and machine learning - Guizao Huang; Guangning Wu; Yujun Guo; Ming Liang; Jun Li; Jinfei Dai; Xianglong Yan; Guoqiang Gao (Journal of Cleaner Production, 2023)

Comparison of two kinds of Agrocybe cylindracea polysaccharides: Structural characteristic and antitumor activity - Chao Liu; Ke-yao Dai; Zhen-tong Li; An-jun Liu (Food and Bioproducts Processing, 2023)

Soil drying legacy does not affect phenanthrene fate in soil but modifies bacterial community response - Jun Zeng; Yanjie Li; Yeliang Dai; Qinghe Zhu; Yucheng Wu; Xiangui Lin (Environmental Pollution, 2023)

A generalized mechanical model with high-flexibility of viscoelastic damping materials and devices considering frequency and amplitude dependence effects - Panpan Gai; Zhaodong Xu; Billie F. Spencer; Jun Dai; Hongwei Li (Engineering Structures, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Potential linkage between WWTPs-river-integrated area pollution risk assessment and dissolved organic matter spectral index - Taoyan Dai; Liquan Wang; Tienan Li; Pengpeng Qiu; Jun Wang; Haotian Song (Environmental Geochemistry and Health, 2023)

Biodegradation of sulfoxaflor and photolysis of sulfoxaflor by ultraviolet radiation - Yun-Xiu Zhao; Ke-Xin Chen; Li Wang; Pan-Pan Yuan; Yi-Jun Dai (Biodegradation, 2023)

Cytotoxic steroids from the stems of Strophanthus divaricatus - Hong-Ling Ran; Sheng-Zhuo Huang; Hao Wang; Li Yang; Cui-Juan Gai; Rui-Jun Duan; Hao-Fu Dai; Ya-Li Guan; Wen-Li Mei (Phytochemistry, 2023)

A label-free fluorescent aptasensor based on a novel exponential rolling circle amplification for highly sensitive ochratoxin A detection - Daozhong Zhu; Ting Huang; Qianying Zhou; Zizhong Yang; Birong Liu; Minmin Li; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Food Chemistry, 2023)

Precisely modulate interfacial Bi-O bridge bond in Co-TCPP/Bi3O4Br to trigger long-lasting charge separation for boosting CO2 photoreduction - Yi Zhang; Fangyu Guo; Keke Wang; Jun Di; Bokki Min; Huiyuan Zhu; Hailong Chen; Yu-Xiang Weng; Jiayu Dai; Yuanbin She; Jiexiang Xia; Huaming Li (Chemical Engineering Journal, 2023)

The presence of soybean, but not soybean cropping frequency has influence on SOM priming in crop rotation systems - Shan-Shan Dai; Peng He; Meng-Yang You; Lu-Jun Li (Plant and Soil, 2023)

Altered dynamic functional connectivity associates with post-traumatic stress disorder - Yingliang Dai; Zhou Zhou; Feng Chen; Li Zhang; Jun Ke; Rongfeng Qi; Guangming Lu; Yuan Zhong (Brain Imaging and Behavior, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

Construction of 3D printed meat analogs from plant-based proteins: Improving the printing performance of soy protein- and gluten-based pastes facilitated by rice protein - Yuxuan Qiu; David Julian McClements; Jun Chen; Changhong Li; Chengmei Liu; Taotao Dai (Food Research International, 2023)

Air-water interfacial properties and quantitative description of pea protein isolate-Tween 20 - Qian Shen; Wei Zheng; Fei Han; Jingnan Zuo; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Linear and nonlinear interface rheological behaviors and structural properties of pea protein (vicilin, legumin, albumin) - Qian Shen; Jing Li; Xiaojun Shen; Xinyu Zhu; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Non-covalent interaction of complex plant protein and betanin: Mechanism of improving thermal stability of betanin - Ting Hu; Taotao Dai; Xuemei He; Lizhen Deng; Ti Li; Jian Sun; Chengmei Liu; Jun Chen (Food Hydrocolloids, 2023)

PFO5DoDA disrupts hepatic homeostasis primarily through glucocorticoid signaling inhibition - Chang Wang; Huayu Fu; Jun Yang; Lei Liu; Fenghong Zhang; Chunyu Yang; Hongyuan Li; Jiamiao Chen; Qi Li; Xiaolin Wang; Yaorui Ye; Nan Sheng; et al. (Journal of Hazardous Materials, 2023)

Role of maturity status on the quality and volatile properties of mango fruits dried by infrared radiation - Dantong Li; Taotao Dai; Mingshun Chen; Ruihong Liang; Wei Liu; Chengmei Liu; Jian Sun; Jun Chen; Lizhen Deng (Food Bioscience, 2023)

Investigation of insecticidal activity of two Rhododendron species on stored-product insects - Yu-Li Sang; Lu Dai; Pei Wang; Li-Jiang Chen; Mei-Ling Jiao; Jing-Yu Liu; Nai-Zhi Zhang; Guang-Wen Fan; Yan-Jun Hao; Xiu-Lan Wang (Journal of Plant Diseases and Protection, 2023)

A double-edged sword: role of apoptosis repressor with caspase recruitment domain (ARC) in tumorigenesis and ischaemia/reperfusion (I/R) injury - Kun Liu; Dongfeng Lan; Chunyang Li; Songpo Liu; Xiaofang Dai; Tao Song; Xianyao Wang; Qinghong Kong; Zhixu He; Jun Tan; Jidong Zhang (Apoptosis, 2023)

The Effect of Smoking Habits on Blood Cadmium and Lead Levels in Residents Living Near a Mining and Smelting Area in Northwest China: a Cross-Sectional Study - Hui Dai; Honglong Zhang; Haiping Wang; Jingping Niu; Bin Luo; Jun Yan; Xun Li (Biological Trace Element Research, 2023)

The effects of seawater thermodynamic parameters on the oxygen minimum zone (OMZ) in the tropical western Pacific Ocean - Jun Ma; Xuegang Li; Jinming Song; Lilian Wen; Qidong Wang; Kuidong Xu; Jiajia Dai; Guorong Zhong (Marine Pollution Bulletin, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Divergent hydrological responses to intensive production under different rainfall regimes: Evidence from long-term field observations - Yiwen Zhou; Zhaoxia Li; Tianwei Wang; Jian Wang; Jun Deng; Yingni Du; Cuiting Dai; Xuanming Zhang; Sijie Zhao (Journal of Hydrology, 2023)

Observation-based sources evolution of non-methane hydrocarbons (NMHCs) in a megacity of China - Yarong Peng; Hongli Wang; Qian Wang; Shengao Jing; Jingyu An; Yaqin Gao; Cheng Huang; Rusha Yan; Haixia Dai; Tiantao Cheng; Qiang Zhang; Meng Li; et al. (Journal of Environmental Sciences, 2023)

Selective catalytic depolymerization of lignin to guaiacols over Mo-Mn/sepiolite in supercritical ethanol - Mingqiang Chen; Wei Dai; Yishuang Wang; Zhiyuan Tang; Hong Li; Chang Li; Zhonglian Yang; Jun Wang (Fuel, 2023)

Effects of pH-shifting treatments on the emulsifying properties of rice protein isolates: Quantitative analysis of interfacial protein layer - Qian Shen; Hongmin Dai; Luming Wen; Wei Zheng; Beixi Li; Jun Dai; Bin Li; Yijie Chen (Food Research International, 2023)

Nonlinear rheological behavior and quantitative proteomic analysis of pea protein isolates at the air-water interface - Qian Shen; Yilun Luo; Wei Zheng; Ting Xiong; Fei Han; Jingnan Zuo; Jun Dai; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Hypoxia mediates Hif-1α to affect myofiber development and Vc regulates the influence by activating Shh-Gli pathway in channel catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Yong-jun Dai; Yang-yang Huang; Mang-mang Wang; Hui-Xing Guo; Wen-Bin Liu; Xiang-fei Li; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Aquaculture, 2023)

Correction to: Involvement of regulation of the excitation:inhibition functional balance in the mPFC in the antidepressant-anxiolytic effect of YL-IPA08, a novel TSPO ligand - Jin Yuan; Jun-Qi Yao; Xin-Xin Fang; Wei Dai; Yun-Hui Wang; Li-Ming Zhang; Yun-Feng Li (Metabolic Brain Disease, 2022)

Analytical formulation for gravitation modeling of mass-heterogeneous bodies - Wen-Yue Dai; Yang Yu; Bin Cheng; Hexi Baoyin; Jun-Feng Li (Journal of Geodesy, 2022)

Hydrogeochemical characterization and water quality assessment in Altay, Xinjiang, northwest China - Juan-Qin Gao; Yang Yu; Deng-Hong Wang; Li-Jun Liu; Wei Wang; Hong-Zhang Dai; Kuang Cen (Environmental Monitoring and Assessment, 2022)

Involvement of regulation of the excitation:inhibition functional balance in the mPFC in the antidepressant-anxiolytic effect of YL-IPA08, a novel TSPO ligand - Jin Yuan; Jun-Qi Yao; Xin-Xin Fang; Wei Dai; Yun-Hui Wang; Li-Ming Zhang; Yun-Feng Li (Metabolic Brain Disease, 2022)

Study on the changes of Structural Covariance Network in post-traumatic stress disorder - Tongtong Xu; Feng Chen; Li Zhang; Yingliang Dai; Jun Ke; Rongfeng Qi; Guangming Lu; Yuan Zhong (Brain Imaging and Behavior, 2022)

Potential Specificity Between Mycorrhizal Fungi Isolated from Widespread Dendrobium spp. and Rare D. huoshanense Seeds - Yan-Jing Tang; Dong-Yu Zhou; Jun Dai; Yang Li; Yong-Mei Xing; Shun-Xing Guo; Juan Chen (Current Microbiology, 2022)

Generalist endophyte Phomopsis liquidambaris colonization of Oryza sativa L. promotes plant growth under nitrogen starvation - Jun Zhou; Peng-Wei Huang; Xin Li; Fabián E. Vaistij; Chuan-Chao Dai (Plant Molecular Biology, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Phomopsis liquidambaris Increases Rice Mineral Uptake Under Waterlogging Condition via the Formation of Well-Developed Root Aerenchyma - Li-Yan Hu; Yang Yang; Hao Wu; Meng-Jun Tang; Xing-Guang Xie; Chuan-Chao Dai (Journal of Plant Growth Regulation, 2022)

Neurovascular abnormalities in retinopathy of prematurity and emerging therapies - Chang Dai; Jun Xiao; Chenguang Wang; Wei Li; Guanfang Su (Journal of Molecular Medicine, 2022)

Biochar-Stimulated Pumpkin Performance Under Cadmium Stress Is Strongly Linked to Metabolite Pattern - Tao Han; Jun Shen; Chunying Dai; Yang Li; Junguo Zhou; Xinzheng Li; Zhiqiang Sun; Zhaorong Mi; Xinyu Miao (Bulletin of Environmental Contamination and Toxicology, 2022)

Four new triterpene glucosides from Salacia cochinchinensis Lour - Lu Gao; Li-Kun Duan; Jin-E Feng; Yun-Tao Jiang; Jun Gao; Jun-Ting Fan; Rong Dai; Zhi-Yong Jiang (Natural Product Research, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

RhoGEF Trio Regulates Radial Migration of Projection Neurons via Its Distinct Domains - Chengwen Wei; Mengwen Sun; Xiaoxuan Sun; Hu Meng; Qiongwei Li; Kai Gao; Weihua Yue; Lifang Wang; Dai Zhang; Jun Li (Neuroscience Bulletin, 2022)
The radial migration of cortical pyramidal neurons (PNs) during corticogenesis is necessary for establishing a multilayered cerebral cortex. Neuronal migration defects are considered a critical etiology of neurodevelopmental disorders, including autism spectrum disorders (ASDs), schizophrenia, epilepsy, and intellectual disability (ID). TRIO is a high-risk candidate gene for ASDs and ID. However, its role in embryonic radial migration and the etiology of ASDs and ID are not fully understood. In this study, we found that the in vivo conditional knockout or in utero knockout of Trio in excitatory precursors in the neocortex caused aberrant polarity and halted the migration of late-born PNs. Further investigation of the underlying mechanism revealed that the interaction of the Trio N-terminal SH3 domain with Myosin X mediated the adherence of migrating neurons to radial glial fibers through regulating the membrane location of neuronal cadherin (N-cadherin). Also, independent or synergistic overexpression of RAC1 and RHOA showed different phenotypic recoveries of the abnormal neuronal migration by affecting the morphological transition and/or the glial fiber-dependent locomotion. Taken together, our findings clarify a novel mechanism of Trio in regulating N-cadherin cell surface expression via the interaction of Myosin X with its N-terminal SH3 domain. These results suggest the vital roles of the guanine nucleotide exchange factor 1 (GEF1) and GEF2 domains in regulating radial migration by activating their Rho GTPase effectors in both distinct and cooperative manners, which might be associated with the abnormal phenotypes in neurodevelopmental disorders.

Simulation of the pollution abatement behavior of regional metal-related enterprises based on the interactive perspective of industrial agglomerations and emission reduction effects - Li-Xin Xiong; Jia-Jun Ning; Yun-He Dong; Meng-Meng Dai (Environmental Geochemistry and Health, 2022)

Morphological description of desiccation cracks in soils: insights from the perspective of anisotropy - Bei-Bing Dai; Jun Yang; Feng-Tao Liu; Chao-Sheng Tang; Tian-Qi Li (Bulletin of Engineering Geology and the Environment, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

Distinct Bottom-Water Bacterial Communities at Methane Seeps With Various Seepage Intensities in Haima, South China Sea - Xiaopeng Li; Zehan Dai; Pengfei Di; Junxi Feng; Jun Tao; Duofu Chen; Niu Li; Yazi Li (Frontiers in Marine Science, 2021)
Methane seeps are chemosynthetic ecosystems in the deep-sea environment. Microbial community structures have been extensively studied in the seepage-affected sediments and investigation in the water column above the seeping sites is still lacking. In this study, prokaryotic communities in the bottom water about 50 cm from the seabed at methane seeps with various seepage intensities in Haima, South China Sea were comparatively studied by using 16S ribosomal RNA gene sequencing. These sites were assigned based on their distinct methane content levels and seafloor landscapes as the non-seepage (NS) site, low-intensity seepage (LIS) site, and high-intensity seepage (HIS) site. The abundances of the dominant phyla Proteobacteria, Bacteroidetes, and Actinobacteria differed significantly between NS and the two seepage sites ( p < 0.05). Alpha diversity differed among the three sites with the HIS site showing the lowest community diversity. Principal component analysis revealed highly divergent bacterial community structures at three sites. Many environmental variables including temperature, alkalinity, pH, methane, dissolved organic carbon (DOC), and inorganic nutrients were measured. Redundancy analysis indicated that methane content is the key environmental factor driving bacterial community variation ( p = 0.001). Linear discriminant analysis effect size analysis identified various differentially enriched genera at the LIS and HIS sites. Phylogenetic analysis revealed close phylogenetic relationship among the operational taxonomic units of these genera with known oil-degrading species, indicating oil seepage may occur at the Haima cold seeps. Co-occurrence networks indicated that the strength of microbial interactions was weakest at the HIS site. This study represents a comprehensive comparison of microbial profiles in the water column of cold seeps in the SCS, revealing that the seepage intensity has a strong impact on bacterial community dynamics.

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Transcriptomic responses of haloalkalitolerant bacterium Egicoccus halophilus EGI 80432T to highly alkaline stress - Dai-Di Chen; Manzoor Ahmad; Yong-Hong Liu; Shuang Wang; Bing-Bing Liu; Shu-Xian Guo; Hong-Chen Jiang; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Transcriptome analysis of wolf spider Pardosa laura exposed to beta-cypermethrin - Qing Ning; Jing Li; Li-hua Wang; Yu-jun Dai; Chang-chun Li (International Journal of Tropical Insect Science, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Study on strength characteristics and mechanism of loess stabilized by F1 ionic soil stabilizer - Jian-dong Li; Xu Wang; Yan-jie Zhang; Dai-jun Jiang; De-ren Liu; Jing-long Wang (Arabian Journal of Geosciences, 2021)

QTL mapping for foxtail millet plant height in multi-environment using an ultra-high density bin map - Qiang He; Hui Zhi; Sha Tang; Lu Xing; Suying Wang; Haigang Wang; Aiying Zhang; Yuhui Li; Ming Gao; Haijin Zhang; Guoqiu Chen; Shutao Dai; et al. (Theoretical and Applied Genetics, 2021)

Injectable collagen scaffold promotes swine myocardial infarction recovery by long-term local retention of transplanted human umbilical cord mesenchymal stem cells - Qiang Wang; Xiaojun He; Bin Wang; Jun Pan; Chunying Shi; Jie Li; Liudi Wang; Yannan Zhao; Jianwu Dai; Dongjin Wang (Science China Life Sciences, 2021)

Distinct Effects of Social Stress on Working Memory in Obsessive-Compulsive Disorder - Qianqian Li; Jun Yan; Jinmin Liao; Xiao Zhang; Lijun Liu; Xiaoyu Fu; Hao Yang Tan; Dai Zhang; Hao Yan (Neuroscience Bulletin, 2021)
Stress might exaggerate the compulsion and impair the working memory of patients with obsessive-compulsive disorder (OCD). This study evaluated the effect of stress on the cognitive neural processing of working memory in OCD and its clinical significance using a “number calculation working memory” task. Thirty-eight patients and 55 gender- and education-matched healthy controls were examined. Stress impaired the performance of the manipulation task in patients. Healthy controls showed less engagement of the medial prefrontal cortex and striatum during the task under stress versus less stress, which was absent in the patients with OCD. The diagnosis × stress interaction effect was significant in the right fusiform, supplementary motor area, precentral cortex and caudate. The failure of suppression of the medial prefrontal cortex and striatum and stress-related hyperactivation in the right fusiform, supplementary motor area, precentral cortex, and caudate might be an OCD-related psychopathological and neural response to stress.

Moisture effects on the active prokaryotic communities in a saline soil unraveled by 18O-informed metagenomics - Yeliang Dai; Yanshuo Pan; Yue Sun; Jun Zeng; Guangming Liu; Wenhui Zhong; Xuanzhen Li; Yucheng Wu; Xiangui Lin (Journal of Soils and Sediments, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

Microbial activity was greater in soils added with herb residue vermicompost than chemical fertilizer - Meirong Lv; Jingjuan Li; Weixin Zhang; Bo Zhou; Jun Dai; Chi Zhang (Soil Ecology Letters, 2020)

Source partitioning of oxygen‐consuming organic matter in the hypoxic zone of the Chesapeake Bay - Jianzhong Su; Wei‐Jun Cai; Jean Brodeur; Najid Hussain; Baoshan Chen; Jeremy M. Testa; K. Michael Scaboo; Deb P. Jaisi; Qiang Li; Minhan Dai; Jeffrey Cornwell (Limnology and Oceanography, 2020)
We surveyed the carbonate system along the main channel of the Chesapeake Bay in June 2016 to elucidate carbonate dynamics and the associated sources of oxygen‐consuming organic matter. Using a two endmember mixing calculation, chemical proxies, and stoichiometry, we demonstrated that in early summer, dissolved inorganic carbon (DIC) dynamics were controlled by aerobic respiration in the water column (43%), sulfate reduction in the sediment (39%), atmospheric CO 2 invasion (13%), and CaCO 3 dissolution (5%). A mass balance of the DIC concentration and its stable isotope suggested that the apparent δ 13 C of oxygen‐consuming organic matter was −19.4 ± 0.3‰. The bulk composition of particulate organic matter also reflected a dominance of algal material (C/N = ~ 6, δ 13 C > −25‰). Therefore, we concluded that the decomposition of autochthonous organic matter (i.e., eutrophication‐stimulated primary production) was the dominant process consuming oxygen, while allochthonous organic matter (terrestrially derived) made minor contributions to oxygen consumption in the hypoxic zone in June 2016. These findings in the Chesapeake Bay contrast with another hypoxic estuarine ecosystem, the Pearl River Estuary in China where allochthonous organic matter contributed significantly to oxygen consumption. The differences between these two systems in terms of hydrology, quantity and quality of organic matter, and physical characteristics are discussed to yield new insights on the formation and maintenance of hypoxia. In both systems, autochthonous organic matter dominates oxygen depletion, indicating that nutrient management and reduction are useful actions to control and mitigate the occurrence of hypoxia for the restoration of ecosystem.

Epidural Spinal Cord Stimulation Promotes Motor Functional Recovery by Enhancing Oligodendrocyte Survival and Differentiation and by Protecting Myelin after Spinal Cord Injury in Rats - Gang Li; Zhong-Kai Fan; Guang-Fei Gu; Zhi-Qiang Jia; Qiang-Qiang Zhang; Jun-Yu Dai; Shi-Sheng He (Neuroscience Bulletin, 2020)

Comparative genomics analysis of Nitriliruptoria reveals the genomic differences and salt adaptation strategies - Dai-Di Chen; Ye Tian; Jian-Yu Jiao; Xiao-Tong Zhang; Yong-Guang Zhang; Zhou-Yan Dong; Meng-Jie Xiong; Min Xiao; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2020)

Collagen-binding basic fibroblast growth factor improves functional remodeling of scarred endometrium in uterine infertile women: a pilot study - Peipei Jiang; Xiaoqiu Tang; Huiyan Wang; Chenyan Dai; Jing Su; Hui Zhu; Minmin Song; Jingyu Liu; Ziqing Nan; Tong Ru; Yaling Li; Jingmei Wang; et al. (Science China Life Sciences, 2019)

P-Rex1 Overexpression Results in Aberrant Neuronal Polarity and Psychosis-Related Behaviors - Qiongwei Li; Lifang Wang; Yuanlin Ma; Weihua Yue; Dai Zhang; Jun Li (Neuroscience Bulletin, 2019)

The Verticillium dahliae Sho1‐MAPK pathway regulates melanin biosynthesis and is required for cotton infection - Jun‐Jiao Li; Lei Zhou; Chun‐Mei Yin; Dan‐Dan Zhang; Steven J. Klosterman; Bao‐Li Wang; Jian Song; Dan Wang; Xiao‐Ping Hu; Krishna V. Subbarao; Jie‐Yin Chen; Xiao‐Feng Dai (Environmental Microbiology, 2019)
Summary Verticillium dahliae is a soil‐borne fungus that causes vascular wilt on numerous plants worldwide. The fungus survives in the soil for up to 14 years by producing melanized microsclerotia. The protective function of melanin in abiotic stresses is well documented. Here, we found that the V . dahliae tetraspan transmembrane protein VdSho1, a homolog of the Saccharomyces cerevisiae Sho1, acts as an osmosensor, and is required for plant penetration and melanin biosynthesis. The deletion mutant Δ Sho1 was incubated on a cellophane membrane substrate that mimics the plant epidermis, revealing that the penetration of Δ Sho1 strain was reduced compared to the wild‐type strain. Furthermore, VdSho1 regulates melanin biosynthesis by a signalling mechanism requiring a kinase‐kinase signalling module of Vst50‐Vst11‐Vst7. Strains, Δ Vst50 , Δ Vst7 and Δ Vst11 also displayed defective penetration and melanin production like the Δ Sho1 strain. Defects in penetration and melanin production in Δ Sho1 were restored by overexpression of Vst50 , suggesting that Vst50 lies downstream of VdSho1 in the regulatory pathway governing penetration and melanin biosynthesis. Data analyses revealed that the transmembrane portion of VdSho1 was essential for both membrane penetration and melanin production. This study demonstrates that Vst50‐Vst11‐Vst7 module regulates VdSho1‐mediated plant penetration and melanin production in V . dahliae , contributing to virulence.

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Study on the efficiency of phytoremediation of soils heavily polluted with PAHs in petroleum-contaminated sites by microorganism - Liqun Hou; Rui Liu; Na Li; Yuanyuan Dai; Jun Yan (Environmental Science and Pollution Research, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Spectral characteristics of copper-stressed vegetation leaves and further understanding of the copper stress vegetation index - Chengye Zhang; Huazhong Ren; Xiujuan Dai; Qiming Qin; Jun Li; Tianyuan Zhang; Yuanheng Sun (International Journal of Remote Sensing, 2019)

Hsc70 Interacts with β4GalT5 to Regulate the Growth of Gliomas - Guan Sun; Ying Cao; Xueliang Dai; Min Li; Jun Guo (NeuroMolecular Medicine, 2019)

A new insecticidal havanensin-type limonoid from the roots of Trichilia sinensis Bentv. - Shou-Bai Liu; Hui-Qin Chen; Gang Feng; Zhi-Kai Guo; Cai-hong Cai; Jun Wang; Wen-Li Mei; Hao-Fu Dai (Natural Product Research, 2018)

Proteomic discovery of H2O2 response in roots and functional characterization of PutGLP gene from alkaligrass - Juanjuan Yu; Yongxue Zhang; Junming Liu; Lin Wang; Panpan Liu; Zepeng Yin; Siyi Guo; Jun Ma; Zhuang Lu; Tai Wang; Yimin She; Yuchen Miao; et al. (Planta, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Association of rs4552569 and rs17095830 single-nucleotide polymorphisms with susceptibility to ankylosing spondylitis in east Asian population: a meta-analysis - Shutao Gao; Huan Wang; Chuankun Zhou; Ming Guan; Xiao Li; Jun Dai; Yinshuang Zou; Huang Fang (Journal of Genetics, 2018)

Molecular cloning of adipose triglyceride lipase (ATGL) gene from blunt snout bream and its expression after LPS-induced TNF-α factor - Yong-Jun Dai; Wen-Bin Liu; Xiang-Fei Li; Man Zhou; Chao Xu; Yu Qian; Guang-Zhen Jiang (Fish Physiology and Biochemistry, 2018)

Segmentation by domestic visitor motivation: Changbai Mountain Biosphere Reserve, China - Xiao-ping Gu; Bernard J. Lewis; Li-jun Niu; Da-pao Yu; Li Zhou; Wang-ming Zhou; Zhen-cai Gong; Zhi-juan Tai; Li-min Dai (Journal of Mountain Science, 2018)

Oxygenated derivative is more influential than unsubstituted polycyclic aromatic hydrocarbon on ammonia-oxidizing archaea in an acidic soil - Yeliang Dai; Yucheng Wu; Qingmin Ding; Jun Zeng; Xuanzhen Li; Jinwei Zheng; Xiangui Lin (Journal of Soils and Sediments, 2018)

Selective toxicity of the mesoionic insecticide, triflumezopyrim, to rice planthoppers and beneficial arthropods - Jun Zhu; Yao Li; Hua Jiang; Chen Liu; Weiwei Lu; Wei Dai; Jianxiang Xu; Fang Liu (Ecotoxicology, 2018)

The effects of rainfall regimes and terracing on runoff and erosion in the Three Gorges area, China - Qin-xue Xu; Pan Wu; Jun-feng Dai; Tian-wei Wang; Zhao-xia Li; Chong-fa Cai; Zhi-hua Shi (Environmental Science and Pollution Research, 2018)

Auxin, Cytokinin, and Ethylene Involved in Rice N Availability Improvement Caused by Endophyte Phomopsis liquidambari - Xin Li; Jun Zhou; Ri-Sheng Xu; Mei-Yao Meng; Xiao Yu; Chuan-Chao Dai (Journal of Plant Growth Regulation, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Construction and characterization of a bacterial artificial chromosome library for Camellia sinensis - Yuling Tai; Hao Wang; Chaoling Wei; Ling Su; Min Li; Liqun Wang; Zhaozhao Dai; Lingyun Shao; Jiayue Jiang; Meizhong Luo; Hua Yang; Weiwei Deng; et al. (Tree Genetics & Genomes, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

A novel diarylheptanoid-bearing sesquiterpene moiety from the rhizomes of Alpinia officinarum - Na Wei; Zhonglin Zhou; Qing Wei; Yong Wang; Jun Jiang; Junqing Zhang; Lixiang Wu; Shuiping Dai; Youbin Li (Natural Product Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

AM1 is a potential ABA substitute for drought tolerance as revealed by physiological and ultra-structural responses of oilseed rape - Muhammad Shahbaz Naeem; Lulu Dai; Farooq Ahmad; Ashfaq Ahmad; Jun Li; Chunlei Zhang (Acta Physiologiae Plantarum, 2016)

The impact of Yangtze River discharge on the genetic structure of a population of the rock bream, Oplegnathus fasciatus - Yongshuang Xiao; Daoyuan Ma; Ming Dai; Qinghua Liu; Zhizhong Xiao; Jun Li; Jing Liu; Shihong Xu; Qiqun Cheng (Marine Biology Research, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Neuroglobin Attenuates Beta Amyloid-Induced Apoptosis Through Inhibiting Caspases Activity by Activating PI3K/Akt Signaling Pathway - Yu Li; Yu-bing Dai; Jie-yun Sun; Yue Xiang; Jun Yang; Song-yang Dai; Xiong Zhang (Journal of Molecular Neuroscience, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Pollen variation as a response to hybridisation in Populus L. section Aigeiros Duby - Ju Tian; Junhao Wang; Li Dong; Fei Dai; Jun Wang (Euphytica, 2015)

New sesquiterpenoid derivatives from Solanum septemlobum with cytotoxicities - Lei Zhang; Hai-Qing Lin; Gui-Sheng Li; Xi-Dian Yue; Sheng-Jun Dai (Natural Product Research, 2015)

Sedimentary and sequence-stratigraphic characteristics of the lower second submember, Shahejie formation, M1 block, Wenmingzhai oilfield, Dongpu depression, China - Xue Li; Jinliang Zhang; Jun Xie; Cunlei Li; Yunjiao Dai; Weilu Li; Yi Zhang; Shasha Li (Arabian Journal of Geosciences, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Stable oxygen isotopes reveal distinct water use patterns of two Haloxylon species in the Gurbantonggut Desert - Yue Dai; Xin-Jun Zheng; Li-Song Tang; Yan Li (Plant and Soil, 2015)

Monitoring the land subsidence with persistent scatterer interferometry in Nansha District, Guangdong, China - Minsi Ao; Changcheng Wang; Rongan Xie; Xingqing Zhang; Jun Hu; Yanan Du; Zhiwei Li; Jianjun Zhu; Wujiao Dai; Cuilin Kuang (Natural Hazards, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Diffusion Source Detection of Volcanic Ash Cloud Using MODIS Satellite Data - Cheng-Fan Li; Yang-Yang Dai; Jun-Juan Zhao; Jing-Yuan Yin; Dan Xue; Shi-Qiang Zhou (Journal of the Indian Society of Remote Sensing, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

New eudesmane-type sesquiterpenoid from Solanum lyratum with cytotoxic activity - Xiu-Ping Nie; Fang Yao; Xi-Dian Yue; Gui-Sheng Li; Sheng-Jun Dai (Natural Product Research, 2014)

Bacillus thuringiensis subsp. sichuansis strain MC28 produces a novel crystal protein with activity against Culex quinquefasciatus larvae - Peng Guan; Xiaojuan Dai; Jun Zhu; Qiao Li; Shuangcheng Li; Shiquan Wang; Ping Li; Aiping Zheng (World Journal of Microbiology and Biotechnology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Production of ramoplanin analogues by genetic engineering of Actinoplanes sp. - Hai-Xue Pan; Zhou-Zhou Chen; Lei Shao; Ji-An Li; Jun-Sheng Chen; Chun-Bao Zhu; Gong-Li Tang; Dai-Jie Chen (Biotechnology Letters, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Visible-light-induced photocatalytic reduction of Cr(VI) with coupled Bi2O3/TiO2 photocatalyst and the synergistic bisphenol A oxidation - Juan Yang; Jun Dai; Jiantong Li (Environmental Science and Pollution Research, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Genetic manipulation revealing an unusual N-terminal region in a stand-alone non-ribosomal peptide synthetase involved in the biosynthesis of ramoplanins - Hai-Xue Pan; Ji-An Li; Lei Shao; Chun-Bao Zhu; Jun-Sheng Chen; Gong-Li Tang; Dai-Jie Chen (Biotechnology Letters, 2013)

Immunological effects of a 10-μg dose of domestic hepatitis B vaccine in adults - Jing-jing Ren; Xue-wei Dai; Zheng-gang Jiang; Ling-zhi Shen; Yong-di Chen; Qian Li; Wen Ren; Ying Liu; Jun Yao; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2012)

Pseudonocardia nantongensis sp. nov., a novel endophytic actinomycete isolated from the coastal halophyte Tamarix chinensis Lour - Ke Xing; Sheng Qin; Guang-Kai Bian; Yue-Ji Zhang; Wen-Di Zhang; Chuan-Chao Dai; Chang-Hong Liu; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2012)

Dynamics and functions of CD4+CD25high regulatory T lymphocytes in Chinese rhesus macaques during the early stage of infection with SIVmac239 - Shao-You Li; Hou-Jun Xia; Zheng-Xi Dai; Gao-Hong Zhang; Bo Fan; Ming-Hua Li; Rui-Rui Wang; Yong-Tang Zheng (Archives of Virology, 2012)

Characterization of HbEREBP1, a wound-responsive transcription factor gene in laticifers of Hevea brasiliensis Muell. Arg. - Yue-Yi Chen; Li-Feng Wang; Long-Jun Dai; Shu-Guang Yang; Wei-Min Tian (Molecular Biology Reports, 2012)

Fertilization increases paddy soil organic carbon density - Shao-xian Wang; Xin-qiang Liang; Qi-xiang Luo; Fang Fan; Ying-xu Chen; Zu-zhang Li; Huo-xi Sun; Tian-fang Dai; Jun-nan Wan; Xiao-jun Li (Journal of Zhejiang University-SCIENCE B, 2012)

Key parameter optimization and analysis of stochastic seismic inversion - Zhe-Yuan Huang; Li-Deng Gan; Xiao-Feng Dai; Ling-Gao Li; Jun Wang (Applied Geophysics, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Molecular cloning and characterization of caprine calpastatin gene - Dai Hua Wang; Gang Yi Xu; Deng Jun Wu; Cheng Li Zheng (Molecular Biology Reports, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

New norditerpenoid alkaloids from Scutellaria barbata with cytotoxic activities - Sheng-Jun Dai; Wei-Bing Peng; Li Shen; De-Wu Zhang; Yan Ren (Natural Product Research, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

Age-related variations of leptin receptor expression in the growth plate of spine and limb: gender- and region-specific changes - Xin-Feng Li; Jun Yan; Lei-Sheng Jiang; Li-Yang Dai (Histochemistry and Cell Biology, 2011)

Improvement of spinosad production by overexpression of gtt and gdh controlled by promoter PermE* in Saccharopolyspora spinosa SIPI-A2090 - Hai-Xue Pan; Ji-An Li; Ning-Jun He; Ji-Ye Chen; Yu-Meng Zhou; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2011)

Molecular characterization and association analysis of porcine adipose triglyceride lipase (PNPLA2) gene - Li He Dai; Yuan Zhu Xiong; Si Wen Jiang; Jun Feng Chen (Molecular Biology Reports, 2011)

Characterization of a wheat HSP70 gene and its expression in response to stripe rust infection and abiotic stresses - Ying-Hui Duan; Jun Guo; Ke Ding; Shu-Juan Wang; Hong Zhang; Xi-Wei Dai; Yue-Ying Chen; Francine Govers; Li-Li Huang; Zhen-Sheng Kang (Molecular Biology Reports, 2011)

Design, expression and characterization of recombinant hybrid peptide Attacin-Thanatin in Escherichia coli - Li Na Wang; Bing Yu; Guo Quan Han; Jun He; Dai Wen Chen (Molecular Biology Reports, 2010)

Genomic structure and evolution of the Pi2/9 locus in wild rice species - Liangying Dai; Jun Wu; Xunbo Li; Xuejun Wang; Xionglun Liu; Chatchawan Jantasuriyarat; Dave Kudrna; Yeisoo Yu; Rod A. Wing; Bin Han; Bo Zhou; Guo-Liang Wang (Theoretical and Applied Genetics, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Groundwater discharge to the Changjiang River, China, during the drought season of 2006: effects of the extreme drought and the impoundment of the Three Gorges Dam - Zhi-jun Dai; Jin-zhou Du; Ao Chu; Jiu-fa Li; Ji-yu Chen; Xiao-ling Zhang (Hydrogeology Journal, 2010)

Genetic variation within and among populations of Orychophragmus violaceus (Cruciferae) in China as detected by ISSR analysis - Li-Jun Zhang; Si-Lan Dai (Genetic Resources and Crop Evolution, 2010)

Two new eudesmane-type sesquiterpenoids from Olanum lyratum - Sheng-Jun Dai; Li Shen; Yan Ren (Natural Product Research, 2009)

Development and application of SCAR markers for sex identification in the dioecious species Ginkgo biloba L. - Liqin Liao; Jun Liu; Yanxia Dai; Qian Li; Ming Xie; Qijiong Chen; Huaqun Yin; Guanzhou Qiu; Xueduan Liu (Euphytica, 2009)

Microcalorimetric Study on the Effect of Ce3+ on Halobacterium halobium R1 - Yi Liu; Jun Yin; Ran Li; Li Li; Jie Dai; Ye-Zhong Zhang; Ping Shen (Biological Trace Element Research, 2008)

A Male Reproduction-Related Kazal-Type Peptidase Inhibitor Gene in the Prawn, Macrobrachium rosenbergii: Molecular Characterization and Expression Patterns - Jun-Xia Cao; Jie-Qiong Dai; Zhong-Min Dai; Guo-Li Yin; Wei-Jun Yang (Marine Biotechnology, 2007)